Heretical Sects as Victims of Hermeneutics: A Study on the Metamorphosis of Religious Practices in the Indonesian Islamic Preaching Institute (LDII) - Khotijah, Yayuk Siti (GoAcademica Research & Publishing, 2024)
One of the da'wah organizations that continues to grow with a large number of followers spread across several regions in Indonesia is the Indonesian Islamic Da'wah Institute/Lembaga Dakwah Islam Indonesia (LDII). LDII's religious stance in recent years has sparked mass rejection from the public, as it is perceived to have deviated from Islamic teachings. This article serves as the central theme of a study aimed at describing and examining the existence of LDII and its quite controversial religious practices. The data collection methods used in this research include observation, interviews, and library research. The findings of this study indicate that LDII, as one of the religious sects in Indonesia, has fallen into deviations in its religious practices due to misunderstandings in comprehending and interpreting true religious messages, resulting from the misuse of the hermeneutic method.